The impact of a takeover bid on the capital market efficiency - Anita Knezovic; Maria Culjak (UTMS Journal of Economics, 2018)
The impact of the announcement of a takeover bid has been widely tested in foreign literature. Therefore, the main goal of this paper is to research the impact of the announcement of a takeover bid on the share price movements in the Croatian capital market and whether the results are consistent to the results achieved in foreign markets. A survey was carried out in the period from 2008 to 2017. Previously, there was no consistent compliance of the target firms with the obligation to disclose information about takeovers to the public. It has been shown that disclosure of the intent to announce a takeover bid affects the share prices of the target company, which is consistent with the results of previous research. Interestingly, most of the price increases occurred before the event day, which directly implies inside trading. However, the purpose of this paper was not a research of use of inside information for trading, which is certainly a recommendation for some of the following research. Considering that was researching impact of the share prices on disclosure of information related to a takeover bid, capital market efficiency was indirectly tested.
Keywords: G34; G41; 330; event study; abnormal returns; corporate control